التعليم الرقمي في ظل كوفيد-19 :تحديات تعليم اللغة العربية للناطقين بغيرها في اجامعات الماليزية - Ashwaq Mohammad Salleh; Hanan Saleh; ManalJusoh @ Mohamad Daud; Nawal Abdullah (Universiti Sains Islam Malaysia, 2024)
3 rd INTERNATIONAL SEMINAR ON ISLAM AND SCIENCE 2020 (SAIS 2020) COVID-19: IMPLICATION, IMPACT AND SOLUTION Date: 15 October 2020 Organized by: Persatuan Kakitangan Akademik USIM (PKAUSIM) In Collaboration with: International Halal and Fatwa Centre (iFFAH) & Fakulti Syariah dan Undang-Undang (FSU)